2010
DOI: 10.28945/1167
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Barriers to Women and Minorities in Computer Science and Information Systems Studies: Results from a Multi-Methodolical Study Conducted at Two Minority Serving Institutions

Abstract: The under representation of women and minorities in undergraduate computer science and information systems programs is a pervasive and persistent problem in the United States. Needed is a better understanding of the background and psychosocial factors that attract, or repel, minority students from computing disciplines. An examination of these factors is the focus of this multimethodological study that has been conducted over three phases with three separate populations.During phase 1, a survey was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…These findings are similar to those of Varma [59] and Buzzetto-More et al [11] who found only a small percentage of CS and engineering students believed that their high school computing courses prepared them for a CS degree. Some of these subjects mentioned that their informal learning influenced them to pursue the CS degree.…”
Section: Prior Experiencesupporting
confidence: 89%
“…These findings are similar to those of Varma [59] and Buzzetto-More et al [11] who found only a small percentage of CS and engineering students believed that their high school computing courses prepared them for a CS degree. Some of these subjects mentioned that their informal learning influenced them to pursue the CS degree.…”
Section: Prior Experiencesupporting
confidence: 89%
“…The need for more opportunities for students to learn CS in high school is particularly pronounced for female students and students from racial and ethnic groups historically underrepresented in computing and technology (URG). Buzzetto-More and colleagues found that inadequate programming skills from coursework prior to college is a barrier to minorities participating in computing disciplines in college [14]. The College Board has reported that students who take AP computer science are eight times more likely to major in CS [15].…”
Section: Related Researchmentioning
confidence: 99%
“…We would like to find out the barriers and key issues that keep women feeling as a minority when they join our course. A barrier that keeps women from pursuing the computer science degree is that female students have less prior experience with computers than men do upon entering the computer science degree [8,9,10]. Further responses revealed that the male respondents played more computer games, taught themselves to program more often, and attended CoderDojo more than the female respondents.…”
Section: Qualitative Datamentioning
confidence: 99%